Integrated simulations of CO2 spreading and pressure response in the multilayer saline aquifer of South Scania Site, Sweden. Issue 4 (11th January 2016) - Tian, Liang; Yang, Zhibing; Jung, Byeongju; Joodaki, Saba; Erlström, Mikael; Zhou, Quanlin; Niemi, Auli
Abstract: An integrated modeling approach/workflow, in which a series of mathematical models of different levels of complexity are applied to evaluate the geological storage capacity of the Scania Site, southwest Sweden, is presented. The storage formation at the site is a layered formation limited by bounding fault zones, and injection is assumed to take place from one existing deep borehole into all layers. A semi‐analytical model for two‐phase flow is first used to evaluate the pressure response and related parameter sensitivity, as well as the first estimates of acceptable injection rates. These results are then used to guide the more detailed numerical simulations that address both pressure response and plume migration. The vertical equilibrium (VE) model is used to obtain a preliminary understanding of the plume migration with a larger number of simulations. Finally the full TOUGH2/ECO2N simulations are performed for the most detailed analyses of pressure responses and plume migration. Throughout, the results of the different modeling approaches are compared to each other. It is concluded that the key limiting factor for the storage capacity at the site in the injection scenario considered is the fast CO2 migration within the high permeability layer. Future studies can address alternative injection scenarios, including using horizontal injection wells and injection to other layers than the high permeability layer.